Letter : Messrs. Martins, Granville Street - Newland, G. M.
038-0095-001 BASQUE CHILDREN'S COMMITTEE CHAIRMAN: THE DUCHESS OF ATHOLL, D.B.E., D.C.L. VICE-CHAIRMEN: MISS ELEANOR RATHBONE, M.P. H.V. TEWSON, ESQ. HON. SECRETARIES: Mr. WILFRID ROBERTS, M.P. LT.-COL. J.R.J. MACNAMARA, M.P. Mr. D.R. GRENFELL, M.P. HON. TREASURER: VISCOUNT CECIL OF CHELWOOD, P.C. K.C. ORGANISING SECRETARY: DR. BETTY MORGAN. 30, ECCLESTON STREET, LONDON, S.W.1. TELEPHONE: SLOANE 9866 HVT/FC/EK/1174. May 24th, 1939. H.V. Tewson, Esq., Trades Union Congress, Transport House, Smith Square, London, S.W.1. Dear Mr. Tewson, Messrs. Martins, Granville Street. Thank you for your letter of May 22nd, enclosing a copy of a letter sent to the Secretary of the Trades Council by the local Secretary of the National Union of Leather Workers. As the children will shortly be leaving Elford Hall, possibly the question of apprenticeship by this firm will not arise but we shall be glad to have further particulars when they come to hand. Yours sincerely, G.M. Newland for Organizing Secretary. 292/946/38/95